SPECIES COMPOSITION OF ICHTHYOFAUNA OF DITCHES OF FERGANA DISTRICT (Scientific journal of the Fergana State University, 2024)
Studies on the study of ichthyofauna of ditches in the Fergana District have not been conducted yet. This article talks about the current species composition of the ichthyofauna of the ditches of the Fergana District. According to the research results, 8 fish species were recorded in the ditches of the Fergana District. Four of them are considered indigenous species, and it was found that Schizothorax eurystomus and Triplophysa strauchii are the dominant species.